(untitled) (Fiep Bulletin - online, 2012)
Background: The heteronormativity, the binarism and stereotypes of gender reflect into discriminatory practices, including homophobic expressions. Intolerance and contempt for those men and women who have different identities and orientation occurs in various scenarios causing a direct effect on reducing the access opportunities and obstacles to the exercise of human rights. In the health area must be ensured human, equalitarian attention without prejudice and discrimination. Aim: analyze the access to health services according to the perception of individuals with homoaffective orientation Methodology: Qualitative research, realized in Joao Pessoa city, Paraiba State. The semi-structured interview was elected as technique of investigation involving eight subjects with homoaffective orientation. The empirical material was submitted to the Technique of Analysis of Content, thematic modality. Results: it was observed that the discrimination is present in the health services, making the problems of the homoaffective population invisible; the professionals of health are not prepared to attend the diversities; the process of normalization, at the same time which generates parameters for the guarantee of rights, can also be used to generate new perimeters of exclusion. Conclusion: The omission denied constitutes as the biggest proof in which the diversity is not yet respected, causing discriminatory acts and removal of this population of the health services. It is considered, therefore, that the promotion of equity must be rethought in terms of guaranteeing the protection of the human and social rights of these populations, since the stigmatization and discrimination are compromising the exercise of citizenship, among them, access to health services.